(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2024)
The official definition of ‘genocide’, given in 1948 by the U.N., also includes ‘forcibly transferring children of the group to another group’. During the Greek civil war (1944-1949) two highly controversial events occurred. On the one hand, there was the forced evacuation of approximately 30.000 children (sons of anti-communists, monarchists and nationalists) from the northern territories, controlled by the Democratic Army of Greece (D.A.G.), to ‘socialist re-education camps’, located in neighbouring communist countries. On the other hand, another controversial aspect was the transfer of approximately 25.000 children (mostly sons of D.A.G. fighters) to villages called ‘children’s cities’, located in southern Greece and managed by religious organisations under the patronage of Queen Frederica of Hanover. Some testimonies suggest that indoctrination into nationalism and monarchism was very frequent.